(untitled) (Baghdad Science Journal, 2011)
The aim of this research is to determine the uranium concentration and its distribution in many sheep organs that live in different region of Iraq. The uranium concentration in tissue samples is measured by using fission tracks registration in CR-39 detector that caused by the bombardment of U235 with thermal neutrons from (241Am-Be) neutron source of thermal flux (5x 103 n.cm-2. s-1). The results show that the maximum uranium concentration in bronchiole tissues of the animals was found in Karbala city (3.706ppm) while the minimum concentration (0.127 ppm) was found in Al-Faluja city, also the same result in lung tissue the maximum value was found in Karbala city (2.313ppm) and the minimum concentration in Al Fluja (0.082). Otherwise, the maximum concentration in liver tissue was found in AdDiwaniyah city (1.156ppm) while the minimum concentration in Al Fluja city (0.153ppm). The uranium concentrations in heart tissues were found various than the previous results. The results of average uranium concentration in each animal were ranged from 0.149 to 1.675 ppm, the maximum values were found in the cities in south region of Iraq.